Separation of tocopherols and tocotrienols from palm fatty acid distillate using hydrolysis-neutralization-adsorption chromatography method - Chu, B.S.; Baharin, B.S.; Quek, S.Y.; Che Man, Y.B. (Blackwell Publishing Inc.subscrip@blackwellpub.com, 2003)
Vitamin E from palm fatty acid distillate (PFAD) was concentrated in this study by removing the extraneous matters, especially free fatty acids (FFA) and acylglycerols. Original PFAD used in this study contained 85 and 13.7% of FFA and acylglycerols, respectively. Acylglycerols in PFAD were first hydrolyzed using commercially available immobilized Candida antarctica lipase at 60C for 6 h. The fatty acids liberated, together with the existing FFA were then removed by neutralization. Hydrolysis followed by neutralization step concentrated vitamin E from an initial amount of 0.37 to 4.32%. Hydrolysis was an important step as without hydrolysis, neutralization could only concentrate vitamin E to 1.80%. Oil extracted from hydrolyzed and neutralized PFAD was then subjected to a normal-phase silica adsorption chromatography. The column was first eluted with hexane followed by isopropanol. A large amount of acylglycerols was removed during the first elution, while vitamin E was desorbed by isopropanol, with a recovery of >90%. Vitamin E concentration after hydrolysis, neutralization and adsorption chromatography was 15.2%. The method described in this study offers an alternative for the existing separation methods. It could be applied as one of a series of steps in producing high-purity vitamin E concentrates.